Analisis serat pangan, indeks glikemik, dan beban glikemik pada food bar tepung mocaf, tepung daun kelor, dan tepung ikan kembung - Devia Amanda Putri; Ibnu Malkan Bakhrul Ilmi (Poltekkes Kemenkes Aceh, 2026)
Background: Diabetes Mellitus (DM) is a disease that occurs when the body cannot use insulin effectively, resulting in increased glucose levels in the bloodstream. According to the Indonesian Ministry of Health, the prevalence of diabetes mellitus in Indonesia reached 45.3 million in 2023. One strategy for DM management is the consumption of foods with a low glycemic index (GI). Low-GI foods help control blood glucose levels and are beneficial for the prevention and management of diabetes mellitus. Foods with high dietary fiber content generally have lower GI values. Food bars are considered functional snack alternatives with potential benefits for DM prevention. Objectives: This study aimed to analyze the dietary fiber content, glycemic index, and glycemic load of a food bar.Methods: An experimental laboratory design with a crossover approach was used. The research was conducted at the Nutrition Laboratory of UPN “Veteran” Jakarta and Saraswanti Indo Genetech (SIG) from June to August and involved 10 UPNVJ student subjects who metthe inclusion criteria off being male or female, aged 18-23 years, BMI 18.5-22.9 kg/m2, no history of DM, and normal fasting blood glucose levels ranging from 70-115 mg/dl. The dietary fiber content was analyzed using the gravimetric method, and the glycemic index was determined using the IAUC method. Data were analyzed using the Shapiro-Wilk normality test and Paired Sample T-Test.Results: The average dietary fiber content of the food bars was 11.26% per 100 g. The GI value obtained was 29.54 (low category), and the glycemic load was 10.92 ( upper limit of the low category). The difference test showed that p<0,001 indicating a significant difference between the reference and test foods.Conclusion: Food bars had high dietary fiber content and low GI values.